اقتراح نموذج لمتابعة وتقييم الأداء الفعلي لإدارة عملية صيانة المباني في الجامعات الحكومية وفق نظرية الأداء المتوازن (حالة جامعة تشرين) - ميا, رنا; جراد, فايز; المزاوي, سناء (Latakia University Journal -Engineering Sciences Series, 2019)
This research provides model to monitor and evaluate of maintenance management performance in governmental universities through the evaluation of the actual case study. Where it Proposed standards to monitor and evaluate of maintenance management performance according to balanced scorecard theory elements: (Internal processes, Customer, Innovation & Growth, Financial) be use Quantitative and Qualitative indicators. In conclusion the application of the proposed model on five different colleges in Tishreen University has proved high efficiency as model to monitor and evaluate of maintenance management performance. Designs checklists were used to help in the elements state evaluation of the building and define maintenance preference from danger to least danger state, calculation maintenance state average was between fair and good (3.85-2.97), also users satisfactions about the quality of service was (70%). Performance value was defined for buildings elements according to (Internal processes, Innovation & Growth, Financial) and for actual performance value to maintenance management of building in Tishreen University. يقدم هذا البحث نموذج يساعد في عملية متابعة وتقييم أداء إدارة الصيانة في الجامعات الحكومية من خلال تقييم الواقع الفعلي لحالة الدراسة حيث تم اقتراح معايير متابعة وتقييم الأداء وفق المحاور الأربعة لنظرية الأداء المتوازن وهي:(العمليات الداخلية، التعلم والنمو، رضا الزبون، المحور المالي) وباستخدام مجموعة مؤشرات كمية ونوعية. ولقد أثبت النموذج المقترح فعالية عالية كنموذج لمتابعة وتقييم الأداء بتطبيقه على عينة من خمس كليات مختلفة في جامعة تشرين، حيث تمَّ تصميم قوائم تفحص لتساعد في فحص حالة العناصر وتحديد أولويات الصيانة المقترحة حسب خطورة الحالة، وحساب متوسط حالة الصيانة للعينة المدروسة والتي تراوحت بين مقبولة إلى جيدة (2.97-3.85 )، كما تم تحديد رضا الموظفين عن إجراءات وخدمات الصيانة المقدمة من خلال استبيان وكانت النتيجة حوالي (70%) وتم أيضاً تحديد قيمة الأداء لمحور العمليات الداخلية ومحور التعلم والنمو والمحور المالي ، وتحديد قيمة الأداء الفعلي النهائية لإدارة عملية صيانة المباني في جامعة تشرين.